Does hematology rotation impact the interest of internal medicine residents in considering hematology as a career? - Mamoun Hassan Sharief; Assem A. Elghazaly; Abdullah Mohammad Al Abbas; Raed Saleh Al Basri; Samy A. Alsirafy (BMC Medical Education, 2024)
Abstract Background The ongoing need for hematologists is not met in many parts of the world. The hematology rotation during internal medicine residency is an opportunity to attract more physicians to the hematology field. This study aimed to assess the impact of a hematology rotation on internal medicine residents’ interest in considering a hematology career. Methods Internal medicine residents were invited to complete an anonymous questionnaire before and after a mandatory hematology rotation. Their interest in pursuing a hematology career was assessed by asking them to rate “Consider hematology as a career” on a 0 to 10 scale (0 = never, 10 = strongly agree). In addition, viewing the hematology workload as manageable, comfort in dealing with cancer and satisfaction with the hematologist lifestyle were assessed before and after the rotation. Results Sixty out of 62 IM residents completed the pre- and post-hematology rotation questionnaire (response rate 97%). 80% were in the age range of 25–29 years and 73% were males. Two-thirds were in the senior level (3rd and 4th year) of their residency program and 40% had a prior rotation in a hematology unit. Rating considering hematology as a career increased significantly from a median of 7 (IQR: 5–9) pre-rotation to 8.5 (IQR: 7–10) post-rotation (p = 0.0018). Subgroup analysis showed a significant increase in interest among subgroups except residents > 29 years of age, those with prior hematology rotation and junior residents (1st and 2nd year residency). The change in viewing hematology workload as manageable, comfort in dealing with cancer patients and perceiving the hematologist lifestyle as satisfactory were strongly positively correlated with the change in considering hematology as a career (p = 0.0014, < 0.0001 and < 0.0001; respectively). Conclusions A hematology rotation is associated with an increase in the interest of internal medicine residents in considering hematology as a career. Further research is needed to Identify factors that may make hematology rotations an effective tool in attracting residents to the hematology field.